Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Komitmen Organisasi dan Kompensasi Terhadap Kinerja Karyawan Pada Pembangkit Listrik Tenaga Mini Hidro PT. Hidro Rizki Ilahi Lebakbarang: Dibuat Oleh Muhammad Sahihrul Fuad, Muhammad Yusuf, Teguh Purwanto - Teguh Purwanto; muh fuad; muh yusuf (Neraca, 2022)
This study aims to examine the effect of leadership style, work motivation, organizational commitment and compensation on employee performance at mini hydro power plant of PT. Hidro Rizki Ilahi, Lebakbarang. All staffs totaling 60 people were as the population and samples as well by the sampling techniques. Some interviews and questionnaires were conducted as the data collecting. Meanwhile, multiple linear regression using SPSS (Statistical Product and Service Solutions) version 21 program was used to analyse the data. From the analysis results, it showed; (1) leadership style has a significant effect on employee performance with a significance value of 0.014 <0.05, (2) work motivation has no significant effect on employee performance with a significance value of 0.140>0.05, (3) organizational commitment has no significant effect on employee performance with a significance value of 0.402> 0.05, (4) compensation has a significant effect on employee performance with a significance value of 0.000 <0.05, and (5) leadership style, work motivation, organizational commitment and compensation simultaneously have a significant effect on employee performance with a significance value of 0.000 <0.05.